Karyotype analysis from four species of edible plants in northeastern Thailand (Biodiversitas Journal of Biological Diversity, 2021)
Karyotype analysis from four species of edible plants, namely one species from family Cannaceae (Canna indicaL.), one species including 2 variants from family Araceae (Colocasia esculenta(L.) Schott, green taro and black taro) and two species from family Apiaceae (Eryngium foetidum L. and Centella asiatica (L.) Urb.) in Maha Sarakham province, northeastern Thailand were determined from root tips. The results showed that the chromosome numbers and karyotype formulae were 2n= 28 = 14m + 10sm + 4st (2sat) with NF = 56 for green taro, 2n= 42 = 20m+ 20sm + 2st (3sat) with NF = 84 for black taro, 2n = 18 = 18sm with NF = 36 for Centella asiatica (L.) Urb., 2n = 16 = 2m +14 sm with NF = 32 for Eryngium foetidum L., 2n= 27 = 2m+ 25sm with NF = 54 for Canna indica L. Both taros had differences in the chromosome numbers and karyotype formulae. The chromosomes of both taros were the asymmetrical karyotype. While, the chromosome structure of both taros, including the number of metacentric, submetacentric and subtelocentric as well as the position of satellite-chromosomes, were found to be different, which indicated inter-and intra-specific variations in this species. Therefore, the chromosome number, karyotype formula, chromosome structure, position of satellite-chromosomes and idiogram can be used for classification of both taros in this study. Moreover, idiograms of both taros were reported for the first time. The karyotype, NF,  RL, CI and ideogram of Centella asiatica(L.) Urb., Eryngium foetidum L. and Canna indica L. were reported for the first time.
Keywords: Edible plants; Chromosome number; Karyotype; Ideogram